Kinematical analysis along maximal lactate steady state swimming intensity - Figueiredo, P.; Nazario, R.; Sousa, M.; Pelarigo, J. G.; Vilas-Boas, J. P.; Fernandes, R. (Journal of Sports Science & Medicine, 2014)
The purpose of this study was to conduct a kinematical analysis during swimming at the intensity corresponding to maximal lactate steady state (MLSS). Thirteen long distance swimmers performed, in different days, an intermittent incremental protocol of n x 200 m until exhaustion and two to four 30-min submaximal constant speed bouts to determine the MLSS. The video analysis, using APAS System (Ariel Dynamics Inc., USA), allowed determining the following relevant swimming determinants (in five moments of the 30-min test: 0, 25, 50, 75, and 100%): stroke rate, stroke length, trunk incline, intracyclic velocity variation, propelling efficiency, index of coordination and the time allotted to propulsion per distance unit. An ANOVA for repeated measures was used to compare the parameters mean values along each moment of analysis. Stoke rate tended to increase and stroke length to decrease along the test; a tendency to decrease was also found for intracyclic velocity variation and propelling efficiency whereas the index of coordination and the propulsive impulse remained stable during the MLSS test. It can be concluded that the MLSS is not only an intensity to maintain without a significant increase of blood lactate concentration, but a concomitant stability for some biomechanical parameters exists (after an initial adaptation). However, efficiency indicators seem to be more sensitive to changes occurring during swimming at this threshold intensity.